Rapid Metabolism of Propylene by Pea Seedlings - Beyer, Elmo M. (1978)
Propylene uptake by intact pea seedlings (Pisum sativum L. cv. Alaska) was easily detected using standard gas chromatographic techniques suggesting rapid metabolism. Comparative studies with highly purified (14)C(3)H(6) and (14)C(2)H(4) under aseptic conditions verified that propylene was rapidly metabolized and indicated that some aspects of its metabolism were similar to that of ethylene since (14)C(3)H(6), like (14)C(2)H(4) (Beyer, Nature 1975, 255: 144-147), was oxidized to (14)CO(2) and incorporated into water-soluble tissue metabolites. However, (14)C(2)H(6) was metabolized at a substantially faster rate and unlike (14)C(2)H(4) the rate of (14)C(3)H(6) tissue incorporation exceeded its rate of oxidation to (14)CO(2). In addition the neutral (14)C-metabolites derived from (14)C(3)H(6) were chromatographically distinct from those formed from (14)C(2)H(4).